Rekomendasi Terbaik 9 Jenis Tanaman Sebagai Bahan Dasar Zat Aktif Pembuatan Gel Serum Anti Jerawat - Andi Permana Permana; Nisa Nur Azizah; Shofia Difa Aulia; Nia Yuniarsih Yuniarsih (Ridwan Institute, 2022)
The development of the cosmetic industry that continues to increase has resulted in various circulations of serum products on the market, both in terms of brands, facilities, types, prices, and variations contained in these products. This fact makes it difficult for some consumers, especially those who do not understand about facial serum, to find facial serum products that are suitable for skin conditions. The use of herbal ingredients is an effort to reduce the side effects of cosmetics. This review aims to provide information about several types of plants that can be used as basic ingredients in the form of the active substance of this anti-Acne serum gel. This review is taken from several national and international journals released in the period from 2009 to 2021. There are various plants that have activity as antibacterial or anti-Acne active substances, namely Averrhioa limbi Linn, Pluchea Indica L, Carica Papaya L, Ocimum Basilicum L, Mangifera Indica L, Garcinia Mangostana L, Citrus Aurantifolia (CA), Annona Muricita L dan Muntingia Calabura L, Citrullus Lanatus Thunb. Some of these plants can be used as basic ingredients for making serum because they have excellent antibacterial activity.